speech Act in Theatrical Discourse - Kalthum Khalid Ahmed; Azad Ahmad Mahmood (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The speech act theory is considered one of the most important topics of research in linguistics. It can be defined as the idea that contains the meaning of the words, which are used outside of language. Language is a mean of performing various functions, called speech acts. Speech act theory proposes that the meaning of what we utter is influenced by the type of speech, the structure of the discourse, and the context in which it is used. This theory originated by John Austen, it explains, how speech can create an action or consequence. The theory is part of the field of pragmatics, which is the study of how language is used in a social context. A speech act is any utterance that serves a function in communication. For example, speech can be used to make statements, ask questions, plead, describe, or persuade, etc.. Within the act of speaking, words are used to do something, not just utter something.